Color‐Discriminating Retinal Configurations of Sensory Rhodopsin I by Photo‐Irradiation Solid‐State NMR Spectroscopy1. (20th May 2014) - Yomoda, Hiroki; Makino, Yoshiteru; Tomonaga, Yuya; Hidaka, Tetsurou; Kawamura, Izuru; Okitsu, Takashi; Wada, Akimori; Sudo, Yuki; Naito, Akira
Abstract SRI (sensory rhodopsin I) can discriminate multiple colors for the attractant and repellent phototaxis. Studies aimed at revealing the color‐dependent mechanism show that SRI is a challenging system not only in photobiology but also in photochemistry. During the photoreaction of SRI, an M‐intermediate (attractant) transforms into a P‐intermediate (repellent) by absorbing blue light. Consequently, SRI then cycles back to the G‐state. The photoreactions were monitored with the 13C NMR signals of [20‐13C]retnal‐SrSRI using in situ photo‐irradiation solid‐state NMR spectroscopy. The M‐intermediate was trapped at −40 °C by illumination at 520 nm. It was transformed into the P‐intermediate by subsequent illumination at 365 nm. These results reveal that the G‐state could be directly transformed to the P‐intermediate by illumination at 365 nm. Thus, the stationary trapped M‐ and P‐intermediates are responsible for positive and negative phototaxis, respectively.